PEMAHAMAN SEJARAH TRANSNASIONAL SEBAGAI SARANA MEMBENTUK INTERNATIONAL-MINDEDNESS - Sajati, Cipta S. (Jazirah: Jurnal Peradaban dan Kebudayaan, 2021)
This study uses a descriptive analytical method through a literature study that explains the understanding of transnational history as a means of forming international-mindedness. The characteristic development is one of the responsibilities of social science to face the 21st century. Social science gives a deep understanding to everyone to know themselves, others, and their position in the global society. The understanding of their position in global society must have coherent with how their past was formed, this is where the history has significance for his endeavor. In the process, history can play a role in shaping an individual to has awareness of international connectivity and global perspective by broadening the perspective of the national historical events through an understanding of transnational history. The understanding of transnational history will look at and compare the context of historical events, especially those that shape national identity, with the perspective between nation and global phenomenon that occurred at that time. International history has some roles and benefits in its study. First, to give a deep understanding regarding social movement. The second, as a complement of the national history reconstruction process, transnational history has the benefit to support the implementation of multicultural-based education design. The last, to understand the context of nationalism as a means of development, and to understand every historical event through an understanding of broader concepts, such as colonialism, feudalism, and slavery